PENGARUH DIGITAL MARKETING, BRAND AWARENESS, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN MEMILIH KULIAH DI UNIVERSITAS KEPANJEN KABUPATEN MALANG - Reni Wahyuningtiyas; Yunus Handoko; Sudjilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The challenges in the current era of higher education or universities are more varied. In addition, the phenomenon of the increasing number of private universities, especially in Malang, reflects the dynamics of change in the national education landscape. As an educational institution managed by the private sector, the survival of private universities is highly dependent on the number of students. The greater the number of students accepted, the more capable the private university is of creating good quality education for its students. There are many strategies carried out by private universities to attract prospective new students. This study aims to determine the Influence of Digital Marketing, Brand Awareness, and Service Quality on the Decision to Choose to Study at Kepanjen University. This research is a quantitative type. The sampling technique used in this study is the purposive sampling method. Data were collected from 160 respondents who were 1st Year Students of the Faculty of Health Sciences, Kepanjen University. The data analysis techniques used were descriptive tests, classical assumption tests, multiple linear regression analysis, determination coefficient tests (R2), t tests and f tests with SPSS for windows 26.0 statistical analysis. The results of multiple linear regression analysis show that Digital Marketing, Brand Awareness, and Service Quality have a positive and significant influence on the Decision to Choose to Study at Kepanjen University, Malang Regency.